Nanostructured Materials for Solar Cell Applications - Tanabe, Katsuaki (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The use of nanomaterials in technologies for photovoltaic applications continues to represent an important area of research. There are numerous mechanisms by which the incorporation of nanomaterials can improve device performance. We invited authors to contribute articles covering the most recent progress and new developments in the design and utilization of nanomaterials for highly efficient, novel devices relevant to solar cell applications. This book covers a broad range of subjects, from nanomaterials synthesis to the design and characterization of photovoltaic devices and technologies with nanomaterial integration.